2023
DOI: 10.1093/nar/gkad614
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mammalian transcription factors that bind to inaccessible chromatin

Abstract: Transcription factors (TFs) are proteins that affect gene expression by binding to regulatory regions of DNA in a sequence specific manner. The binding of TFs to DNA is controlled by many factors, including the DNA sequence, concentration of TF, chromatin accessibility and co-factors. Here, we systematically investigated the binding mechanism of hundreds of TFs by analysing ChIP-seq data with our explainable statistical model, ChIPanalyser. This tool uses as inputs the DNA sequence binding motif; the capacity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 94 publications
2
2
0
Order By: Relevance
“…To validate the remaining 20 PTF predictions, we performed literature searches and found that RFX5 had the ability to displace nucleosomes 14 . In addition, many of the predicted PTFs such as ZKSCAN1, USF1,USF2 and SRF, were confirmed by a recent study 57 .…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…To validate the remaining 20 PTF predictions, we performed literature searches and found that RFX5 had the ability to displace nucleosomes 14 . In addition, many of the predicted PTFs such as ZKSCAN1, USF1,USF2 and SRF, were confirmed by a recent study 57 .…”
Section: Resultssupporting
confidence: 68%
“…Among those with a high PCC > 0.5, were ZKSCAN1, ESR1, NFATC3, ZBTB7B, MAX, and TBX2. Half of them were also predicted to be pioneer by a recent study 57 . With the exception of a few cases, none of transcription factors was identified as being pioneer in all cell types because pioneer activity is often cell- type specific.…”
Section: Resultsmentioning
confidence: 99%
“…The increased frequency of binding motifs related to the central ISR transcriptional regulator ATF4, as well as ATF4 targets, is suggestive that retrograde signaling might have the potential to alter chromatin structure. Indeed, ATF4 is a pioneer factor capable of altering chromatin accessibility (113,114), which could be consistent with the transcriptional signatures observed in metabolic tissues with mitochondrial damage. However, it is unclear how the induction of ATF4 remodels sites of chromatin accessibility that are lost at key markers of β cell maturity, such as NeuroD1 (80).…”
Section: Discussionsupporting
confidence: 80%
“…To validate the remaining 20 PTF predictions, we performed literature searches and found that RFX5 had the ability to displace nucleosomes ( Zhu et al, 2018 ). In addition, many of the predicted PTFs, such as ZKSCAN1, USF1, USF2, and SRF, were confirmed by a recent study ( Pop et al, 2023 ).…”
Section: Resultssupporting
confidence: 72%